2019
DOI: 10.1093/mnras/stz671
|View full text |Cite
|
Sign up to set email alerts
|

A high binary fraction for the most massive close-in giant planets and brown dwarf desert members

Abstract: Stellar multiplicity is believed to influence planetary formation and evolution, although the precise nature and extent of this role remain ambiguous. We present a study aimed at testing the role of stellar multiplicity in the formation and/or evolution of the most massive, closein planetary and substellar companions. Using past and new direct imaging observations, as well as the Gaia DR2 catalogue, we searched for wide binary companions to 38 stars hosting massive giant planets or brown dwarfs (M > 7 M Jup ) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
119
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(145 citation statements)
references
References 200 publications
(360 reference statements)
26
119
0
Order By: Relevance
“…On the other hand, there is a clear tendency towards a very high fraction of hot-Jupiter in moderate-to-wide binaries. For the 50 ≤ ρ ≤ 2000 au separation range, reference [17] indeed find a multiplicity fraction that is 2.9 times higher for hot-Jupiter hosts than for field stars, a result which was confirmed by [19] for close-in companions up to the brown dwarf regime.…”
Section: Characteristics Of Exoplanets In Binariesmentioning
confidence: 63%
“…On the other hand, there is a clear tendency towards a very high fraction of hot-Jupiter in moderate-to-wide binaries. For the 50 ≤ ρ ≤ 2000 au separation range, reference [17] indeed find a multiplicity fraction that is 2.9 times higher for hot-Jupiter hosts than for field stars, a result which was confirmed by [19] for close-in companions up to the brown dwarf regime.…”
Section: Characteristics Of Exoplanets In Binariesmentioning
confidence: 63%
“…We also queried the position of the star in the Gaia DR2 catalogue and searched for comoving sources within a angular radius corresponding to a projected separation of 10 4 AU given the parallax of the star. We define comoving objects in Gaia as sources with a fractional difference of < 20% in parallax and at least one of the proper motion coordinates, following the approach from Fontanive et al (2019) to search for wide binary companions in Gaia DR2. This ensures that binary components showing significant disparities in their kinematics due to their gravitational influence on one another (i.e.…”
Section: Binary Fraction Of ∆µ Starsmentioning
confidence: 99%
“…The VLT/NACO (L filter) and VLT/SPHERE (Y JH + K1K2) 5-σ detection limits were taken from the median performances achieved in Rameau et al (2013) and Maire et al (2017), respectively. The Gaia limit corresponds to the Gaia DR2 99% binary completeness limit described in Fontanive et al (2019). The sensitivity limits in terms of contrast for the future E-ELT/METIS instrument were obtained through end-to-end simulations of a 1-hour observation in the L band for a star of magnitude L = 6, using the classical vortex coronagraph and assuming an ADI sequence with 40 deg parallac-tic angle rotation (B. Carlomagno et al, in prep.).…”
Section: Promising Candidates For Direct Imaging Searchesmentioning
confidence: 99%
“…Bolmont et al 2012). From a sample of 38 high mass (> 7 M J ) exoplanets and brown dwarfs, Fontanive et al (2019) found that companions with orbital periods less than 10 days have circularisation timescales consistent with the Kozai-Lidov mechanism. We have estimated the timescale of the Kozai-Lidov mechanism (τ K L ) for the NGTS-7 system using the formalism from Kiseleva et al (1998) and find τ K L <55 Myr for initial orbits beyond 0.1 AU.…”
Section: Formation Of Ngts-7abmentioning
confidence: 96%